Study on movement law of overburden strata and fracture zone height in deep mining work face - Lu, Changyuan; Zhang, Xuebo; Han, Linxiu (Frontiers in Earth Science, 2023)
In order to accurately determine the location of fracture zone, optimize the design parameters of high-level boreholes, and improve the effect of gas drainage, take the No. 25030 working face of Xuehu Coal Mine, Henan Shenhuo Coal & Power Co., Ltd. as the research object to study the movement law of overburden strata in the working face. To determine the height of ‘vertical three zones’ of overburden strata by combining theoretical calculation, numerical simulation and field test. Through theoretical calculation, the maximum vertical height range of caving zone from coal seam roof is 5.5–9.2 m, and the maximum vertical height range of water flowing fractured zone from coal seam roof is 26.0–37.2 m. Through numerical simulation, the maximum height of the caving zone is 8.0 m from the roof, and the maximum height of the fracture zone is 27.0 m from the roof. Through field test, when the vertical height of the final borehole from the roof of the coal seam is 18.4–30.0 m, the gas concentration extracted by the borehole is generally high. When the vertical height of the borehole is 24.6–28.4 m from the coal seam roof, the gas concentration is in the peak area. The height distribution range of rock “vertical three zones” in Xuehu Mine No. 25030 working face obtained by three methods is roughly similar, and it is suggested to refer to the measured value in the design of goaf gas drainage. The test results show that the gas drainage effect is the best when the vertical distance from the coal seam roof is 24.6–28.4 m, and it is suggested that the high level boreholes should be arranged in this area.